ANALISIS TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN DANA DESA DI DESA PANGALLOANG KABUPATEN BULUKUMBA - Kurniasih, Nurmutaharah Dwi; Anwar, Azwar; Ryketeng, Masdar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to find out and analyze the application of the principles of transparency and accountability in the management of Village Funds in Pangalloang Village, Bulukumba Regency, based on the regulation of the Minister of Home Affairs Number 20 of 2018. The type of research used is descriptive qualitative research. Data was collected through observation, in-depth interviews with village officials and community leaders, and documentation of village financial statements. The results of the study show that: (1) The transparency of the management of Village Funds in Pangalloang Village has been well implemented in the aspect of publication through the APBDesa billboard, but it still needs to be improved in the aspect of passive transparency in the form of providing information boards at each location of physical activities. (2) Accountability at the planning, implementation, administration, and accountability stages is highly accountable by involving the community in Musrenbang and the use of an orderly financial system. However, at the reporting stage, obstacles were still found in the form of delays in the submission of realization reports that exceeded the regulatory deadline. Overall, the management of the Village Fund in Pangalloang Village has tried to meet good governance standards despite several administrative obstacles.